KAMPANYE SOSIAL BIJAK MENGGUNAKAN APLIKASI ONLINE DATING PADA ANAK MUDA MASA KINI DI KOTA PALEMBANG - Ayu Nissa Kharimah; Heri Iswandi; Yosef Yulius (Penerbit dan Percetakan, CV. Picmotiv, 2023)
Abstract: Before the technology was invented, long-distance communication used to rely on written letters, but now with advanced technology, it can be easily done through a stable internet connection on a smartphone. However, the convenience of online dating applications can be misused by irresponsible people, so policies and security measures must be implemented to protect users' privacy and comfort. Cases that occur in the form of fraud, extortion, sexual harassment cause mental health problems. Based on these problems, the author designed a social campaign that aims to educate people in Palembang City to be wiser in using social media. The author conducted a case study by applying the design thinking design method as data analysis to overcome these problems and using the 5W + 1H method (what, why, who, where, why, how). The design media to be used are digital education books, starter dating boxes for women and men, other information media such as posters and Instagram, and supporting media such as notebooks, Tumblr bottles, classic mirror, making, stickers, classic clocks, aromatherapy candles, and calendars.